2021
DOI: 10.18203/2394-6040.ijcmph20210211
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition prevailing trend study among under five children of urban slum area of Gwalior city Madhya Pradesh

Abstract: Background: Under five children constitute the most vulnerable segment and their nutritional status and mortality rate is a sensitive indicator of the community’s health and nutrition. Health indices of slum children are worst among all urban groups and are even poorer than rural average.Methods: A community based cross-sectional study was conducted from October 2019 to January 2020 in urban slum area of Gwalior city. Data were collected from 550 mothers of children aged 6-60 months using pre-tested semi struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Sample size (n=201) was calculated according to the study done by Disha Agarwal et al in Agra (16) by the formula SAMPLE SIZE = (Z-Score)^2 x Standard Deviation x (1-Standard Deviation)/Confidence Interval^2 ; prevalence rate of GDD for 0-11m of 6% with confidence level 95%, acceptable difference of 3%. So, the sample size calculated is 200.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size (n=201) was calculated according to the study done by Disha Agarwal et al in Agra (16) by the formula SAMPLE SIZE = (Z-Score)^2 x Standard Deviation x (1-Standard Deviation)/Confidence Interval^2 ; prevalence rate of GDD for 0-11m of 6% with confidence level 95%, acceptable difference of 3%. So, the sample size calculated is 200.…”
Section: Discussionmentioning
confidence: 99%
“…We were interested in knowing the educational level of both parents and found that it is similar; the majority reported having completed secondary education, i.e., they had concluded the third and final stage of basic education. Some authors refer that educational level of both parents affects the development of language and learning of children 35,36 ; others consider that maternal educational level is essential, and suggest that illiterate or poorly-educated mothers represent a risk factor for the development of LD and LeD 31,[37][38][39] , and that those with higher educational levels represent a protective factor 33 .…”
Section: Discussionmentioning
confidence: 99%
“…But in this globalized world of the twenty-first century, the incidence of undernutrition is experienced by a wide range of pockets across the globe (UNICEF et al, 2019 ). Several studies observed that the bio-demographic and socio-economic factors, such as BMI of mother, marriage age of mother, child birth weight, number of siblings, birth order, food intake, family income, education of parents, sanitation facility, source of drinking water, have a direct bearing in the prevalence of malnutrition of children (de Onis & Blossner, 1997 ; Cummins, 1998 ; Phillips, 2006 ; Kanjilal et al, 2010 ; Panigrahi & Das, 2014 ; Amruth et al, 2015 ; Rengma et al, 2016 ; Ansuya et al, 2018 ; De & Chattopadhyay, 2019 ; Islam & Biswas, 2020 ; Agarwal et al, 2021 ). In this present study, a total number of fifteen bio-demographic and socio-economic parameters are adopted as independent variables to find out the significant predictors of child malnutrition (Table 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is observed from NFHS-3 and NFHS-4 reports that the scenario of child malnutrition in West Bengal is lower than the national average, but the prevalence of malnutrition is not evenly distributed across the districts of the state (IIPS, 2017 , 2021 ). Moreover, there are different studies done considering the role of bio-demographic factors in the prevalence of child malnutrition across the country (Kanjilal et al, 2010 ; Bisai et al, 2014 ; Panigrahi & Das, 2014 ; Amruth et al, 2015 ; Rengma et al, 2016 ; Ansuya et al, 2018 ; Roy et al, 2018 ; De & Chattopadhyay, 2019 ; Agarwal et al, 2021 ). In the present research work, Purulia, one of the poorest districts in terms of Gender Development Index (GDI) and HDI (Government of West Bengal, 2004 ), and Multidimensional Poverty Index (MPI) in West Bengal (National Institute for Transforming India [NITI] Aayog, 2021a ), has been considered to study the prevalence of child malnutrition (Fig.…”
Section: Introductionmentioning
confidence: 99%